Avenida Doutor Ulysses Guimarães: desenvolvimento urbano e a manutenção da periferia - Pinheiro, Rafaela Martin (Universidade Federal de São Carlos, 2025)
This work aims to analyze, in a dialectical way, the changes related to urban development over the years on Avenida Doutor Ulysses Guimarães, based on fundamental concepts of urban geography by authors such as Henri Lefebvre and David Harvey to analyze the impacts caused on the urban development of the city. To carry out the research, primary sources were used with the application of two branches of qualitative-quantitative questionnaires to dialogue directly with the residents of the avenue. Using secondary sources, such as bibliographic and documentary research to understand the social dynamics that shape the center-periphery relations. Urban development and the creation of new road connections generate the movement of subcenters in the North Zone of Sorocaba, causing changes in infrastructure and driving the construction of new centralities in the growing outskirts, devaluing the center and increasing the cost of living in these areas previously belonging to marginalized groups that may be pushed to new outskirts or, as observed in the research, finding ways to maintain themselves in these new imposed conditions by adapting their way of subsisting.
Doctor Ulysses Guimarães Avenue: urban development and maintenance of the periphery.
Keywords: Centro-periferia; Centralidades; Desenvolvimento urbano; Center-outskirts; Centralities; Urban development; CIENCIAS HUMANAS::GEOGRAFIA::GEOGRAFIA HUMANA::GEOGRAFIA URBANA